Pepper Mild Mottle Virus - Scott Adkins; Pamela D. Roberts (EDIS)
Pepper mild mottle virus (PMMoV) occurs worldwide in field-grown bell, hot, and ornamental pepper species. The virus has also been found in greenhouse peppers in Canada, and Spain where greenhouse production practices are ideal for rapid spread of the disease. PMMoV was identified in commercial bell pepper fields in Florida in 2000. Disease incidence (the percentage of plants infected) of up to 30% was estimated in these Florida outbreaks. In subsequent years, PMMoV has appeared only sporadically in the state. Because foliar symptoms can be mild, infected plants may not be noticed until the fruit symptoms are evident, resulting in spread to neighboring plants and higher yield losses.